Proceedings - 33. Workshop Computational Intelligence Berlin, 23.-24. November 2023 - Schulte, Horst; Hoffmann, Frank; Mikut, Ralf (KIT Scientific Publishing, 2023)
The workshop proceedings contain the contributions of the 33rd workshop "Computational Intelligence" which will take place from 23.11. - 24.11.2023 in Berlin. The focus is on methods, applications and tools for Fuzzy systems, Artificial Neural Networks, Evolutionary algorithms and Data mining methods as well as the comparison of methods on the basis of industrial and benchmark problems.